Clíticos e preposições: a norma e o ‘normal’ em jornais paulistas (1900 a 1915) - Berlinck, Rosane de Andrade; Biazolli, Caroline Carnielli (Estudos Linguísticos (São Paulo. 1978), 2016)
This paper is based on the assertions of Theory of Linguistic Variation and Change and proposes a discussion about possible actions of linguistic norms over two variable phenomena in Brazilian Portuguese: the position of clitic pronouns associated with a single verb, and the use of prepositions with verbal complements indicating a “goal/recipient”. We intend to describe each phenomenon by analysing data selected from newspapers from São Paulo and Rio Claro published between 1900 and 1915. We compare the descriptions and evaluate the role played by the standard and the common usage which is (already) perceptible in the ‘paulistas’ published pages of that period.